Associations between balance and muscle strength, power performance in male youth athletes of different maturity status - Hammami, R.; Chaouachi, A.; Makhlouf, I.; Granacher, U.; Behm, D. G. (Pediatric Exercise Science, 2016)
Balance, strength and power relationships may contain important information at various maturational stages to determine training priorities. Purpose: The objective was to examine maturity-specific relationships of static/dynamic balance with strength and power measures in young male athletes. Methods: Soccer players (N = 130) aged 10-16 were assessed with the Stork and Y balance (YBT) tests. Strength/power measures included back extensor muscle strength, standing long jump (SLJ), countermovement jump (CMJ), and 3-hop jump tests. Associations between balance with strength/power variables were calculated according to peak-height-velocity (PHV). Results: There were significant medium-large sized correlations between all balance measures with back extensor strength (r = .486-.791) and large associations with power (r = .511-.827). These correlation coefficients were significantly different between pre-PHV and circa PHV as well as pre-PHV and post-PHV with larger associations in the more mature groups. Irrespective of maturity-status, SLJ was the best strength/power predictor with the highest proportion of variance (12-47%) for balance (i.e., Stork eyes opened) and the YBT was the best balance predictor with the highest proportion of variance (43-78%) for all strength/power variables. Conclusion: The associations between balance and muscle strength/power measures in youth athletes that increase with maturity may imply transfer effects from balance to strength/power training and vice versa in youth athletes.